Sudan - land, climate, energy, agriculture and development: A study in the Sudano-Sahel Initiative for regional development, jobs, and food security - Abdelrahman Khidir Osman; Adil M. Ali (University of Bonn, Center for Development Research (ZEF), 2021)
Sudan is situated in Sub-Saharan Africa, covering an area of about 1.9 million km2 and has a population of 43 million. It is regarded as one of the countries in the world where human development is least advanced with a poverty rate of about 46%. Sudan's economy is based on agriculture, which contributes about one-third of the (GDP). Sudan's agriculture has three distinct crop and three distinct livestock production systems. The Crop production systems are: irrigated, traditional and mechanized rain-fed farming. The livestock production systems are: nomadic, transhumant and sedentary systems. The annual cultivated land is around 20 million hectares, more than 85% of which are rain-fed. The livestock population is estimated at 105 million heads concentrated in nomadic and transhumant production systems. Water resources in Sudan are: river Nile and its tributaries, seasonal streams, underground water and surface water. Sources of energy are: biomass; electricity (hydro and fossil fuels) and petroleum products, accounting for about 78,8% and 14%, respectively, of the total energy balance. Sudan has significant renewable energy resources. Particularly solar energy is well distributed all over the country thus having the potential to facilitate the provision of energy services to rural settlements. [...] Sudan has implemented several plans and policies which directly relate to climate change adaptation and development priorities. The focus of these plans and policies is: food security and raising productivity, reducing poverty and enhancing adaptation and resilience to climate change, protecting and developing natural resources, land tenure problems and strengthening governance and institutional capacity. These interventions had limited success in achieving their objectives. The main reasons are: a lack of political stability and fluctuating economic and financial policies as well as weak administrative and implementation capacity of the government institutions. The main lessons learnt are: agricultural-development programmes require increased and more effective public and private partnershipsinvolving the main stakeholders. The low flow of finance to the agricultural sector remains one of the obstacles of agricultural growth. In addition to the poor rural infrastructure, the ongoing conflicts and social unrest in many parts of the country are strongly impacting the performance of the economy and constraining the development plans and policies.
Keywords: O30; Q24; Q25; Q42; Q54; Q55; Q58; 330; Sahel; energy; climate change; land degradation; innovation; policy